2010
DOI: 10.1038/leu.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Elevated PIN1 expression by C/EBPα-p30 blocks C/EBPα-induced granulocytic differentiation through c-Jun in AML

Abstract: The transcription factor CCAAT enhancer-binding protein a (C/EBPa) has an important role in granulopoiesis. The tumor suppressor function of C/EBPa is shown by the findings that loss of expression or function of C/EBPa in leukemic blasts contributes to a block in myeloid cell differentiation and to leukemia. C/EBPa mutations are found in around 9% of acute myeloid leukemia (AML) patients. The mechanism by which the mutant form of C/EBPa (C/EBPa-p30) exerts a differentiation block is not well understood. By usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 46 publications
2
51
1
Order By: Relevance
“…While our peptide mapping clearly shows specific sites in both TRIB2 and C/EBPα responsible for the direct interaction, in the absence of crystal structure information we cannot predict further based on our data the reason why p30 is not targeted by TRIB2 for degradation. Our data does not discount a role for p30 in TRIB2 mediated AML; p30 presence may, for example, activate a unique set of genes, inhibit other C/EBPs or bind to a unique set of proteins distinct from C/EBPα p42 as previously reported (32,33). Indeed, U937 cells ligases including β-TrCP, COP1 and Smurf1 (36).…”
Section: Discussioncontrasting
confidence: 41%
“…While our peptide mapping clearly shows specific sites in both TRIB2 and C/EBPα responsible for the direct interaction, in the absence of crystal structure information we cannot predict further based on our data the reason why p30 is not targeted by TRIB2 for degradation. Our data does not discount a role for p30 in TRIB2 mediated AML; p30 presence may, for example, activate a unique set of genes, inhibit other C/EBPs or bind to a unique set of proteins distinct from C/EBPα p42 as previously reported (32,33). Indeed, U937 cells ligases including β-TrCP, COP1 and Smurf1 (36).…”
Section: Discussioncontrasting
confidence: 41%
“…Expression levels have been normalized to that of ␤-actin and calculated using the ⌬⌬C T method. Fold change in expression has been calculated for each gene by assuming its expression in untransfected cells is equal to 1. example, it has recently been shown that p30 up-regulates the expression of Ubc9 (32), an E2-Sumo-conjugating protein, and PIN1, peptidyl-prolyl cis/trans-isomerase (33). The up-regulation of Ubc9 does not require binding of p30 to the promoter of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Wulf et al showed that Pin1 transcription was triggered by oncogenic Neu/Ras signaling via E2F activation (Ryo et al, 2002). Although a recent study reported the mutant form (C/EBPα-p30) of the CCAAT enhancer-binding proteinα has a positive effect on Pin1 gene transcription in leukemia cells, C/EBPα-p30 indirectly stimulated Pin1 transcription via an increase in E2F1 recruitment in the gene promoter (Pulikkan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%